Spin Ice‐like Magnetic Relaxation of a Two‐dimensional Network based on Manganese(III) Salen‐type Single‐Molecule Magnets. Issue 49 (9th September 2020) - Kachi‐Terajima, Chihiro; Eiba, Tasuku; Ishii, Rikako; Miyasaka, Hitoshi; Kodama, Yuta; Saito, Toshiaki
Abstract: Spin ice is an exotic type of magnetism displayed by bulk rare‐earth pyrochlore oxides. We discovered a spin ice‐like magnetic relaxation of [Mn(saltmen)4 Mn(CN)6 ](ClO4 )⋅13 H2 O (saltmen 2− =N, N′‐(1, 1, 2, 2‐tetramethylethylene)bis(salicylideneiminate)). This magnetic system can be considered as a two‐dimensional network of Mn III salen‐type single‐molecule magnets (SMMs) in which each SMM unit (ST =4) has two orthogonally oriented axial anisotropies and is connected ferromagnetically through the [Mn(CN)6 ] 3− unit (S=1). This work illustrates that a two‐dimensional SMM network with competition between the ferromagnetic interaction and local noncollinear magnetic anisotropies on SMMs is a new type of magnetic system exhibiting slow relaxation of magnetization with a Davidson‐Cole‐type broad distribution of the relaxation time. Abstract : Spin ice‐like magnetic relaxation was found in a two‐dimensional network of Mn III salen‐type single‐molecule magnets with S T =4. The spin ice‐like behavior was a consequence of the competition between the ferromagnetic interaction and local noncollinear magnetic anisotropies on the single‐molecule magnets.